FRACTURE BEHAVIOR OF ACRYLONITRILE-BUTADIENE-STYRENE RESIN - Husaini Husaini; Kikuo Kishimoto (Mesin, 2000)
In this research, mixed mode loading testing of actylonitrile-butadiene-styrene (ABS) resin was carried out by using a compact tension shear specimen which was attached to a special loading device. The angle between the loading axis and the crack surface was varied from 90o (Mode I) to 0° (Mode I1). Two types of ABS resin were examined. The ï¬rst one (ABS-I) has a butadiene rubber content of 18 wt % in the form of small particles of diameter about 200 nm. The second one (ABS-2) has the same overall butadiene rubber content but a bimodal particle distribution with diameters of 200 nm and 500 nm. Crack initiation and propagation was observed by using a video microscope. The results show that the fracture angle for both materials under mixed mode loading coincides with the values predicted by the maximum hoop stress criterion. To obtain the stress intensity ï¬‚zctors, numerical analyses of compact-tension-shear specimen were conducted using a two dimensional ï¬nite element analysis. Fracture behavior of ABS resins under mixed mode loading was almost the same as that under mode I loading for lower value of mode 11 component. However, for higher mode II component, shear type fracture occurred at initial crack tip.